Nexus Between FDI and Production Indices: Evidence from Asian Countries - Paul, Sujan Chandra; Jahan, Nusrat; Hassan, Md. Mehedi; Mondal, Tandra (Asian Journal of Empirical Research, 2021)
This study aims to explore the effect of foreign direct investment on different types of production indices and some other variables. For this, panel data of 46 countries from Asia was accumulated for the time frame of 1991 to 2018. This paper employed the OLS, POLS, 2SLS, and GMM models. The study reveals that there is a favorable association between foreign direct investment and food production index and fertilizer consumption in all the models used in the study. Livestock production index has significant positive association with foreign direct investment in POLS and GMM models. Crop yield has major positive association with regards to foreign direct investment in all mentioned models except GMM. Land under cereal production has significant positive association in respect of foreign direct investment in OLS and 2SLS models. Crop production index has significant mixed association with foreign direct investment in different models. In POLS model, crop production index and foreign direct investment has significant inverse relationship and in GMM model, crop production index and foreign direct investment has significant positive correlation. Finally, permanent cropland has significant negative relationship with regards to foreign direct investment derived from OLS and 2SLS models.